PENDEKATAN DALAM PENGKAJIAN ISLAM (Konsep Dasar dalam Memahami Ilmu Ke-Islaman perspektif Charles J Adam) - Sahibuddin, Sahibuddin; Subhan, Moh (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2014)
At a period of this modernization of very attractive science studies which are to be studied exhaustively, especially islam. progressively expanding Study of Islam, hence more and more also allow thinker especially among intensive west to be more active in studying it. This matter of caosed that islam shall no longer comprehend only limited to congeniality historically and doktriner or limited to at things having the character of normative, formalism and symbolic. However, having come to a complex phenomenon. Islam not only number in the form of formal guide about how a individual have to mean thier life. By increasing science had by someone hence islam has come to a cultural system, civilization, political community, economics. Altogether that represents the part of its validity of growth of world. So that to study and conduct some approach in Islam a study shall no longger possible only evaluated from one aspect, but requiring of a method and approach of interdisiplinier. Study in approach of study of islam conducted by Charles J. Adams is vital importance to growth in a study of islam by using science in multi dimension and various approaches, so that it can comprehend teaching of islam which is comprehensive. And an idea of Charles J. Adams has contribution in a meaning to development of science who is studying that: First, giving kontribution which is significant in presenting method and solve the problem in the study of islam among academics, especially in approach having the character of inovation to be used by all science. Both of passing idea bargained and method presented by Charles J. Adams can assist all researchers to comprehend religion, good in context of sosio-historis and also of normative-theology.